Musarañas - Roel, Esteban 1969-; Andrés, Juanfer 1975-; Gómez, Macarena 1978-; Tosar, Luis 1971-; Silva, Hugo 1977- (Sony Pictures Home Entertainment, 2015)
"Spain, 1950s. Montse's agoraphobia keeps her locked in a sinister apartment in Madrid and her only link to reality is the little sister she lost her youth raising. But one day, a reckless young neighbor, Carlos, falls down the stairwell and drags himself to their door. Someone has entered the shrew's nest... perhaps he'll never leave."--IMDb